Reconciling forest profitability and biodiversity conservation under disturbance risk: the role of forest management and salvage logging. (4th September 2020) - Augustynczik, Andrey L D; Asbeck, Thomas; Basile, Marco; Jonker, Marlotte; Knuff, Anna; Yousefpour, Rasoul; Hanewinkel, Marc
Abstract: Forest management and disturbances are among the main drivers of changes in forest dynamics in temperate ecosystems. To promote and maintain forest multifunctionality and species persistence in the landscape, it is critical that the interactions between these factors and forest biodiversity are disentangled. Still, the relationships between disturbances and forest management are poorly understood and may hinder an adequate planning of management and conservation actions in these forests. Here we address this issue via a coupled ecological-economic modeling system under different climate change scenarios. We employed data from a large-scale field-based research in southwestern Germany, in combination with a climate-sensitive forest growth model. Thereby, we quantified changes in multiple biodiversity indicators (including richness of birds, bats and flying insect orders) and tree microhabitats (TreMs) in the face of disturbance and management interventions. Our results show that windstorms may cause economic damage in managed forests, but at the same time improve biodiversity indicators in these areas. Salvage logging, however, may dampen these positive impacts for the majority of indicators considered. Moreover, management solutions targeting at wind risk mitigation may be detrimental to some taxa (e.g. forest birds) but still performed better than the business-as-usual management, in terms of the biodiversity indicators applied. We conclude that considering disturbance impacts on forest dynamics will be key to maintain the sustainability in the use of forest resources and support species persistence in temperate forest landscapes.